2023
DOI: 10.3390/ijms24129815
|View full text |Cite
|
Sign up to set email alerts
|

The Thyroid Hormone Axis and Female Reproduction

Abstract: Thyroid function affects multiple sites of the female hypothalamic-pituitary gonadal (HPG) axis. Disruption of thyroid function has been linked to reproductive dysfunction in women and is associated with menstrual irregularity, infertility, poor pregnancy outcomes, and gynecological conditions such as premature ovarian insufficiency and polycystic ovarian syndrome. Thus, the complex molecular interplay between hormones involved in thyroid and reproductive functions is further compounded by the association of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 239 publications
0
7
0
Order By: Relevance
“…In addition, considering the complexity of endocrine system that controls body processes and functions and the well-known link between thyroid and gonads through the hypothalamic-pituitary gonadal axis [ 33 ], mainly in females but evident also in males [ 34 , 35 ], it appeared of interest to investigate the potential impact of HT on thyroid homeostasis. At present, this is the first in vivo study that explores the potential impact of HT on thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering the complexity of endocrine system that controls body processes and functions and the well-known link between thyroid and gonads through the hypothalamic-pituitary gonadal axis [ 33 ], mainly in females but evident also in males [ 34 , 35 ], it appeared of interest to investigate the potential impact of HT on thyroid homeostasis. At present, this is the first in vivo study that explores the potential impact of HT on thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms previous findings (Mazzilli et al, 2023;El-Kashlan et al, 2015;La Vignera et al, 2017) demonstrating testicular dysfunction and male infertility in hypothyroidism. Hyperprolactinemia might be the link between the observed primary hypothyroidism and hypogonadotropic hypogonadism (Brown et al, 2023) since BPF has been shown to increase circulatory prolactin . Hypothyroidism is associated with an increase in circulatory TRH, which in turn increases circulatory prolactin (Tashjian Jr et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal thyroid function and thyroid diseases will adversely affect female reproductive function and lead to abnormal levels of female sex hormones, which will lead to irregular menstruation, infertility, poor pregnancy outcome and premature ovarian failure. [ 51 ] Interestingly, studies have found that there are sex differences in the incidence of gout, and female estrogen and progesterone can reduce the risk of gout. [ 52 ] It also provides some ideas for us to study the relationship between thyroid disease and gout.…”
Section: Discussionmentioning
confidence: 99%